2015
DOI: 10.1097/igc.0000000000000491
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Debulking Surgery in the Management of Advanced Ovarian Cancer After Neoadjuvant Chemotherapy

Abstract: Laparoscopic cytoreduction in patients with advanced ovarian cancer after neoadjuvant chemotherapy, when performed by skilled surgeons, seems feasible and may decrease the impact of aggressive surgery on high-morbidity patients, such as on women after chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…In the following years, reports emerged demonstrating the feasibility of the laparoscopic management of ovarian cancer, but its use has been largely limited to surgeries for diagnosis as well as the assessment of resectability and second-look procedures,25 27–29 and in the staging of select cases of early-stage disease 24 28 30–34. Some studies have also reported on laparoscopic cytoreduction in highly selected patients with advanced ovarian cancer 14–17…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the following years, reports emerged demonstrating the feasibility of the laparoscopic management of ovarian cancer, but its use has been largely limited to surgeries for diagnosis as well as the assessment of resectability and second-look procedures,25 27–29 and in the staging of select cases of early-stage disease 24 28 30–34. Some studies have also reported on laparoscopic cytoreduction in highly selected patients with advanced ovarian cancer 14–17…”
Section: Discussionmentioning
confidence: 99%
“…The use of neoadjuvant chemotherapy followed by interval surgical cytoreduction and adjuvant chemotherapy has become an option for some women with advanced ovarian cancer, offering comparable survival8–11 and decreased morbidity9–13 compared with upfront cytoreductive surgery. Preliminary studies have laid the groundwork on the feasibility of minimally invasive interval cytoreductive surgery in selected patients after neoadjuvant chemotherapy 14–20. Since the Food and Drug Administration’s approval of the da Vinci Surgical System for gynecologic procedures in 2005, it has rapidly integrated into the treatment of uterine cancer and, like laparoscopy, has resulted in reduced operative blood loss, lower incidence of post-operative complications, and faster recovery 21 22…”
Section: Introductionmentioning
confidence: 99%
“…In laparoscopic surgeries, organ injury is the main reason of conversion to open surgery. The conversion rate of laparoscopic staging surgery of EOC was reported to be 4%–10% [ 13 ], or 6.6% in laparoscopic cytoreduction [ 14 ]. In our study, the conversion rate was 3.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Another study of 91 patients selected to undergo interval CRS via robotic surgery or laparotomy showed no difference in survival between the two approaches (13). Several other small-scale, retrospective studies have drawn similar conclusions (17)(18)(19), and on a larger scale, a meta-analysis of 3,231 patients found no significant difference between minimally invasive and open interval CRS in the rate of complete cytoreduction, an important oncological outcome correlating directly with survival (20).…”
Section: Discussionmentioning
confidence: 78%